Research funding for addressing tobacco related disease: an analysis of UK investment between 2008 and 2012 - Hall, Mary; Bogdanovica, Ilze; Britton, John (BMJ Publishing Group Ltd, 2016)
Introduction Tobacco use is the leading cause of preventable death in the UK. However research spending on tobacco related disease, and particularly smoking prevention, is thought to be low. We therefore aimed to assess the relation between tobacco-related research investment and disease burden from 2008 to 2012.